2017
DOI: 10.1186/s13287-017-0572-8
|View full text |Cite
|
Sign up to set email alerts
|

Yields and chondrogenic potential of primary synovial mesenchymal stem cells are comparable between rheumatoid arthritis and osteoarthritis patients

Abstract: BackgroundMesenchymal stem cells derived from the synovial membrane (synovial MSCs) are a candidate cell source for regenerative medicine of cartilage and menisci due to their high chondrogenic ability. Regenerative medicine can be expected for RA patients with the inflammation well-controlled as well as OA patients and transplantation of synovial MSCs would also be a possible therapeutic treatment. Some properties of synovial MSCs vary dependent on the diseases patients have, and whether or not the pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The MSCs obtained from the suspended synovium cultures from RA and OA donors had similar mean harvested cell numbers at passage 0 and passage 1, chondrogenic potential, and surface epitope profiles. We previously reported similar results for a comparison of the properties of synovial MSCs obtained using digested synovial cells from RA and OA donors in a standard cell culture [ 12 ]. This similarity between the current findings from suspended synovium culture and our previous results from standard cell culture is interesting because migrated cells from synovium and digested cells in synovium are seemed to have similar properties.…”
Section: Discussionmentioning
confidence: 63%
“…The MSCs obtained from the suspended synovium cultures from RA and OA donors had similar mean harvested cell numbers at passage 0 and passage 1, chondrogenic potential, and surface epitope profiles. We previously reported similar results for a comparison of the properties of synovial MSCs obtained using digested synovial cells from RA and OA donors in a standard cell culture [ 12 ]. This similarity between the current findings from suspended synovium culture and our previous results from standard cell culture is interesting because migrated cells from synovium and digested cells in synovium are seemed to have similar properties.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have mainly focused on the analysis of the single disorders, and in particular of OA, where it has been shown that bone marrow-derived MSCs show reduced chondrogenic potential [6,7]; alternatively, comparison of the two cartilage disorders with different etiologies have been carried out [26]. MSCs in OP patients have been studied to a lesser extent; however, these studies have shown that bone-marrow-derived MSCs in OP patients can switch their differentiation potential from osteogenesis to adipogenesis, thus possibly contributing to the pathogenesis of OP [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that mesenchymal stem cells isolated from the synovial membrane are reported that a candidate cell source in cartilage and menisci regenerative medicine and OA ( 31 ). Feng et al reported that intra-articular injection of allogeneic adipose-derived mesenchymal stem cells combined with hyaluronic acid could efficiently block OA progression and promote cartilage regeneration and allogeneic adipose-derived mesenchymal stem cells combined with HA might survive at least 14 weeks after intra-articular injection ( 32 ).…”
Section: Discussionmentioning
confidence: 99%